2007
DOI: 10.1186/1475-2891-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient adequacy during weight loss interventions: a randomized study in women comparing the dietary intake in a meal replacement group with a traditional food group

Abstract: BackgroundSafe and effective weight control strategies are needed to stem the current obesity epidemic. The objective of this one-year study was to document and compare the macronutrient and micronutrient levels in the foods chosen by women following two different weight reduction interventions.MethodsNinety-six generally healthy overweight or obese women (ages 25–50 years; BMI 25–35 kg/m2) were randomized into a Traditional Food group (TFG) or a Meal Replacement Group (MRG) incorporating 1–2 meal replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 23 publications
9
60
0
2
Order By: Relevance
“…An acknowledged limitation of the study is that it was for relatively short duration and the dietary intakes were self-reported; however, a comparison between predietary versus post-dietary intake indicated significant diet compliance and caloric reduction. This proposition that a commercial MR can enhance nutrient adequacy is also supported by another recent randomized clinical trial [21]. The study compared the nutrient adequacy between a diet plan using MRs versus another that used traditional food.…”
Section: Mrs and Micronutrients Adequacymentioning
confidence: 87%
See 1 more Smart Citation
“…An acknowledged limitation of the study is that it was for relatively short duration and the dietary intakes were self-reported; however, a comparison between predietary versus post-dietary intake indicated significant diet compliance and caloric reduction. This proposition that a commercial MR can enhance nutrient adequacy is also supported by another recent randomized clinical trial [21]. The study compared the nutrient adequacy between a diet plan using MRs versus another that used traditional food.…”
Section: Mrs and Micronutrients Adequacymentioning
confidence: 87%
“…Across several studies that evaluated micronutrient adequacy, many of the micronutrients that consistently fell short of the recommended daily intake are essential for metabolism, energy, and bone health (B vitamins, iron, calcium, and magnesium) [20][21][22]. The caveats of these studies are that food records were often self-reported and the studies included selected groups (ie, overweight, obese) who usually tend to inaccurately report their true food intakes.…”
Section: Mrs and Micronutrients Adequacymentioning
confidence: 97%
“…Time points calculated as a proportion of the overall study length indicated that the commencement of the study was the most commonly used time point (57.5%, n D 61) for dietary assessment. The second assessment was more likely to be at the midpoint of the study (32.3%, n D 32) , Donaghue et al, 2000, Riddell et al, 2000, Smith-Warner et al, 2000, Davidson et al, 2001, McGavin et al, 2001, Leslie et al, 2002, Shah et al, 2002, Chee et al, 2003, Drummond et al, 2003, Hendriks et al, 2003, Moeller et al, 2003, Sondergaard et al, 2003, Mori et al, 2004, Dyerberg et al, 2004, He et al, 2004, Bhargava et al, 2004, Maskarinec et al, 2004a, Maskarinec et al, 2004b, Shah et al, 2004, Sloth et al, 2004, Tapsell et al, 2004, Waller et al, 2004, Hermansen et al, 2005, Barnard et al, 2006, Chen et al, 2006, Iyer et al, 2006, Marfella et al, 2006, Ashley et al, 2007, Murphy et al, 2007, TurnerMcGrievy et al, 2008, Barnard et al, 2009, Davis et al, 2009) with 25 studies completing their dietary assessments in only two periods of assessment of which only 11 included the endpoint of the study as the final time point. (Barr et al, 2000, Conceicao de Oliveira et al, 2003, Erlund et al, 2003…”
Section: Resultsmentioning
confidence: 99%
“…The individuals may have some difficulties in selecting or cooking the complicated low-calorie menus, in which various factors such as energy, carbohydrates, proteins or fat are involved. Hence, deficiency of macro-and micronutrients can occur [24,25]. Therefore, we aimed to determine the effect on weight loss using a HC meal replacement compared to a HP meal replacement.…”
Section: Introductionmentioning
confidence: 99%